Hematological manifestations and complications of Gaucher disease. Issue 4 (3rd April 2021) - Revel-Vilk, Shoshana; Szer, Jeff; Zimran, Ari
ABSTRACT: Introduction : Gaucher disease (GD), although pan-ethnic and rare (common in Ashkenazi Jews), is of great importance to hematologists both for diagnosis and management. The need for increased awareness of GD is that delayed diagnosis may lead to preventable irreversible complications (mainly skeletal) or unnecessary invasive procedures (e.g. bone marrow biopsy), and the birth of another affected sibling due to lack of genetic consulting. Areas covered : The review outlines the common hematological manifestations of GD, including splenomegaly, thrombocytopenia, and anemia. Other hematological manifestations such as coagulation abnormalities, platelet dysfunction, gammopathy, and other hematological malignancies associated with GD are also discussed. Current and future treatment modalities are delineated, including enzyme replacement and substrate reduction therapy, pharmacological chaperon, and gene therapy. A literature search was conducted to identify original research articles relevant to hematology manifestations and GD published before November 2020. Expert opinion : Patients with GD should be ideally followed and treated in a center of excellence where the GD expert benefits from experienced consultants in relevant disciplines. Due to the availability of several very expensive treatment options, it is important to have an unbiased expert who can select the most suitable management for the individual patients (including withholding prescription in asymptomatic patients).